Determinants of interorganizational employee mobility - Zdrilić, Iva (Economic and business review, 2025)
This article provides a comprehensive overview of the determinants of interorganizational employee mobility and proposes their multilevel typology across different sectors and industries. We conduct a systematic literature review of 158 papers in this field. Our results show that some determinants of employee mobility also appear as mobility effects, closing the “determinants–interorganizational employee mobility–effects” circle. They also show a hierarchy among mobility determinants, different types of interorganizational mobility, and different effects when mobility occurs between competing and cooperating organizations. This study primarily contributes to the career development literature, which recognizes interorganizational mobility as the primary mechanism for achieving individual work–life balance goals. By systematically constructing a multilevel typology of mobility determinants and examining their effects across different sectors and industries, the study’s findings also contribute to labor economics by helping to understand the motivations of mobile employees and mitigate potential negative consequences of such mobility.
Keywords: bibliometric analysis; bibliometrična analiza; employment; job mobility; zaposlitvena mobilnost; zaposlovanje